„ŻELAZNA DZIEWCZYNKA” - „MISS WORLD” - „MADAME NO”: czyli stereotypami malowany obraz kanclerz Niemiec Angeli Merkel w prasie niemieckiej i polskiej “ - Bastian, Michał (Investigationes Linguisticae, 2010)
This article contains the linguistic analysis of the stereotypes moulding the picture of the German chancellor Angela Merkel in the German and Polish press. But first the stereotype as an object of linguistic research is shown to develop a theoretical basis. The analysis is based on articles from on-line editions of German and Polish weeklies, which bring social and political topics up. The stereotypical statements are analysed on the following language planes: the plane of morphology and word formation and also the syntactic plane. Within the confines of the morphologic and word formation analysis I concentrate on noun and adjective because these two parts of speech seem to be of greatest importance in the examined articles.